Quantum mechanics: Concepts and applications - Zettili, Nouredine (Wiley, 2012)
This textbook provides a balanced and modern approach to quantum mechanics. It combines the essential elements of the theory with the practical applications. Containing many examples and problems with step by step solutions, it assists the reader in mastering the machinery of quantum mechanics.